Quetiapine and Wolff-Parkinson-White Syndrome - Michael Chen; Hassaan Gomaa; Alonso Cortez-Resendiz; Christopher Martin; Andrew Francis; Alfredo Bellon (Case Reports in Psychiatry)
Quetiapine is occasionally associated with cardiovascular adverse effects such as QTc prolongation. QTc prolongation is a side effect that requires monitoring in order to avoid more serious cardiac complications. One particular understudied area is the potential for antipsychotics to elicit electroconduction abnormalities in patients with Wolff-Parkinson-White (WPW) Syndrome. In the present report, we describe a case of quetiapine overdose in a patient with WPW.